Daily function, not motor or cognitive status, relates stronger with mobility in people with Parkinson's disease. - Swank, Chad; Criminger, Christina (Physiotherapy Practice & Research, 2020)
INTRODUCTION: Gait engages motor and cognitive neural pathways. However, progressive deterioration of motor and cognitive function is characteristic in Parkinson's disease (PD). We explored relationships between motor impairment, cognitive function, daily functioning, and gait in people with PD. We hypothesized there would be a stronger relationship between walking and cognitive function as gait task complexity increased. METHODS: Community-dwelling participants with PD were assessed on motor impairment [United Parkinson's Disease Rating Scale Motor Subscale (UPDRSm)], cognitive function [Repeatable Battery for the Assessment of Neuropsychological Status (RBANS)], daily function [Schwab & England (S&E) ADL scale] and mobility [Timed Up and Go (TUG)] under single and dual task conditions. Analyses included Spearmans' rank correlations coefficient to determine relational strengths between outcomes and separate forward stepwise multiple linear regressions to predict dual task gait performance. RESULTS: Forty-five participants [age Mean (M) = 68.93±7.78 years; 32 male/13 female; UPDRSm, M = 25.24±11.93] completed this study. RBANS was poorly related to TUGmotor and TUGcognitive. UPDRSm (rho = 0.524; p < 0.001) and S&E (rho = –0.589; p < 0.001) were moderately related to TUGmotor ; S&E (rho = –0.581; p < 0.001) to TUGcognitive. S&E (R2 = 0.234; F (1,43) = 13.14) and RBANS Language subscale (R2 = 0.071; F (1,42) = 4.31) were predictive of TUGmotor performance; S&E of TUGalone (R2 = 0.150; F (1,43) = 7.56) and TUGcognitive performance (R2 = 0.375; F (1,43) = 25.81). CONCLUSIONS: Daily function appears more closely related to dual task mobility than separate assessments of motor and cognitive function in this population.